1998
DOI: 10.1159/000012273
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Aspects of Hyperprolactinemia

Abstract: Patients with hyperprolactinemia often present with emotional difficulties. These occasionally persist even after successful treatment. Insight into the roots of their diseased state makes a difference in the handling of all cases, but becomes crucial in the not-so-rare situations in which the normalization of hormonal levels is not followed by a feeling of cure. This chapter attempts to provide details, discuss and situate in context the following blocks of pertinent information: (1) prolactin acts upon the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 19 publications
0
29
1
8
Order By: Relevance
“…Another retrospective study found no correlation between the two [27]. Hyperprolactinaemia may be associated with subtle psychological symptoms such as anxiety, depression and hostility that occasionally persist even after successful treatment of elevated PRL [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study found no correlation between the two [27]. Hyperprolactinaemia may be associated with subtle psychological symptoms such as anxiety, depression and hostility that occasionally persist even after successful treatment of elevated PRL [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In adult females, this can be manifest as impaired cycling/reduced estrous periods, low libido, premature reproductive senescence, reduced conception rates, increased pre-term fetal losses, prolonged parturitions, smaller birth weights, asymmetrical infant development, increased offspring stress responsiveness, poor maternal care (or infanticide), and/or increased infant mortality. Many of these effects stem directly from HPA axis overactivation, but additional causal factors include stress-induced prolactin elevation [Sobrinho, 1998[Sobrinho, , 2003 and, more speculatively, luteolytic stress-activated protein kinases [as activated by mitogens: Yadav et al, 2001]. Oxytocin, too, is a crucial reproductive and maternal hormone, especially during parturition and in the early stages of maternal care, whose release can be inhibited by stress [see e.g., Leng et al, 1987;Pedersen and Boccia, 2002;Kiecolt-Glaser et al, 2002].…”
Section: Reduced Reproductive Successmentioning
confidence: 99%
“…Variações nas concentrações de prolactina no sistema nervoso central poderiam afetar o humor, as emoções e o bem-estar. Por outro lado, traços da personalidade e fatores externos ambientais podem estimular a secreção de prolactina e ter papel na gênese da doença (Sobrinho, 1998). Dentre o conhecimento de reações psicossomáticas e hiperprolactinemia, um exemplo típico é a pseudociese, que pode ser uma ativação extratemporal do sistema neuroendócrino (Sobrinho, 1993).…”
Section: Hiperprolactinemia E Psiquismounclassified
“…Assies et al (1992), ao avaliarem 14 pacientes hiperprolactinêmicas quanto a aspectos psicossociais, verificaram maior freqüência de separação dos pais na infância quando comparados a 14 mulheres controles. O estresse poderia ser o gatilho de alterações neuroendó-crinas envolvendo dopamina e/ou serotonina, que afetam a liberação de prolactina (Sobrinho, 1998;Freeman et al, 2000). Sonino et al (2004), estudando 52 pacientes com hiperprolactinemia, observaram que estes relatavam significativamente mais eventos pessoais estressantes que os indivíduos controles.…”
Section: Hiperprolactinemia E Psiquismounclassified
See 1 more Smart Citation